The Influence of Gamification on Motivation and Performance: Evidence from Grab Driver Partners - Dina Septiani; Mia Sriwidiyani; Sandi Nasrudin Wibowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of gamification on Grab driver partner motivation and performance and to test the role of motivation as a mediating variable. This study complements the literature related to the influence of gamification in the context of the digital economy in Indonesia, especially in the transportation sector, which is still rarely studied. The research method used is quantitative by distributing questionnaires to 256 Grab driver partners selected by purposive sampling. Data analysis uses Structural Equation Modeling (SEM) on Smartpls 4 software to test the relationship between variables. The results of the study indicate that gamification has a positive and significant influence on driver partner motivation and performance. Motivation is also proven to have a significant influence on performance while mediating the relationship between gamification and performance, although the mediation influence is relatively weak. These findings enrich the discussion on gamification in the transportation service sector and show that the right implementation of gamification can be an influenceive strategy to improve Grab driver partner motivation and performance.